Highway asset management - Yang, Chao (2013)
The aim of this thesis is to provide a framework for a decision making system to operate a highway network, to evaluate the impacts of maintenance activities, and to allocate limited budgets and resources in the highway network. This integrated model is composed of a network level traffic flow model (NTFM), a pavement deterioration model, and an optimisation framework.